EXPERT MODEL OF CHILDREN'S HEALTH AS A BASIS FOR THE CONSTRUCTION OF INTERDISCIPLINARY MONITORING - S.M. Chechel'nitskaya; A.A. Mikheeva; M.V. Timakova; V.T. Finagin; A.G. Rumyantsev ("Paediatrician" Publishers LLC, 2008)
For the purpose of provision of wide range of specialists with authentic information about health state of children and ado les cents it's necessary to create new systems of their observation, based on interdisciplinary principles. An expert model of health, which gives a basis for a construction of such systems, is described in this article. 132 experts took part in this trial; they were doctors, psychologists, teachers, philosophers, sociologists, and elder adolescents and adults independently of their profession. A del phi method was used in this expert model. A factorial analysis was used for a classification of health indicators and factors, which influence on it. A detailed nominal expert classification was suggested, and the state of health can be estimated on the basis of it as an object, having definite behaviors and depending of some external factors. A nominal expert classification includes 36 indices of state of health and 37 factors, influencing on it. An ordinal expert classification was obtained as a result of factorial analysis, which allows estimation of significance level of every index. Key words: health, monitoring, expert questionnaires, heath monitoring.